The Chandra X-ray Observatory : exploring the high energy universe - Wilkes, B. (Belinda); Tucker, Wallace H. (AAS-IOP astronomy. Release 2., 2020)
NASA's Chandra X-Ray Observatory has ushered in a revolution in X-ray astronomy. Over the last two decades Chandra has captured stunning celestial X-ray images, measured spectra and monitored light curves to reveal and map the hottest, most energetic regions of the universe. Celebrating its 20th anniversary, this book includes current reviews of the major discoveries and scientific results made by Chandra, authored by leading experts in each sub-field. Documenting the progress, discoveries and developments implemented by the mission, this book provides its readers with a comprehensive review of the mission thus far and its potential future implications. The book includes beautiful images of celestial sources generated from Chandra and multi-wavelength data. 3D figures, movies and interactive illustrations are also used throughout to enhance the text.